Beyond text: ChatGPT as an emotional resilience support tool for Gen Z – A sequential explanatory design exploration - Kavitha, Krishnan; Joshith, V. P; Sharma, Sonal (E-learning and digital media, 2024)
In the digital era, Artificial Intelligence (AI) has arisen as a revolutionary influence with the potential to transform multiple spheres of human life. Chatbots, particularly OpenAI's Chat Generative Pre-trained Transformer (ChatGPT), are increasingly recognised as promising tools in diverse aspects, including mental health. This study delves into ChatGPT's effectiveness as an emotional resilience support tool specifically for Generation Z (Gen Z), a demographic deeply engaged in digital interactions. Employing a sequential explanatory design that integrates quantitative and qualitative analyses, the research investigates Gen Z users' perceptions of ChatGPT's effectiveness, barriers to its utilisation, and impact on emotional resilience. The findings reveal a significant acknowledgement of ChatGPT's role in enhancing emotional well-being and notable concerns regarding privacy and security. Further, qualitative insights underscore the significance of personalised interactions, nonjudgmental space, and active listening characteristics of ChatGPT in fostering emotional resilience. Moreover, the study identifies key areas for improvement, such as expanded topic coverage and cultural representation. Educational stakeholders and mental health professionals are encouraged to utilise these insights to integrate ChatGPT and other AI tools into tailored support frameworks for Gen Z.